Poverty rate and government income transfers: A spatial simultaneous equations approach - Jeanty, P. Wilner; Ulimwengu, John M. (International Food Policy Research Institute, 2011)
The poverty rate and income transfer are clearly correlated. However, not much research has attempted to determine the causal linkage between the two. Previous research has primarily focused on the poverty-reducing impact of income transfer. In this paper, we apply a simultaneous equation system of spatial regressions to uncover the spatial pattern of the relationship between the poverty rate and income transfer, using a sample of 3,001 U.S. counties. The results are in line with theoretical expectations; they provide evidence of a significant simultaneity effect between the poverty rate and income transfer. Our findings also confirm the presence of significant spatial autocorrelation. Contrary to previous studies, we find that more generous counties tend to do a better job of reducing poverty and that counties with more poor tend to be less generous, creating incentive for the poor to participate in the labor force. Furthermore, counties located in devolution states perform better in both poverty reduction and income transfer. These findings are missing from extant literature that focuses only on the poverty-reducing impact of welfare payments.